PENGARUH TEKNOLOGI INFORMASI DAN MODAL INTELEKTUAL TERHADAP EFEKTIVITAS KOMUNIKASI SERTA IMPLIKASINYA PADA KINERJA KARYAWAN PT. KURNIA PURNAMA JAYA - Muhammad Jaka Wiratama; Nurdasila Darsono; Teuku Rolli Ilhamsyah Putra (Jurnal Manajemen Inovasi, 2017)
ABSTRACTThe purpose of this study was to determine: (1) analyze the conditions of information technology, intellectual capital, the effectiveness of the communication and performance of employees (2) the influence of information technology and intellectual capital, influence simultaneously and partially on the effectiveness of communication, (3) the influence of information technology and capital intellectual influence simultaneously and partially on employee performance PT. Kurnia Purnama Jaya (4) the effect of information technology and intellectual capital to employee performance through effective communication PT. Kurnia Purnama Jaya  and (5) Effect of communication effectiveness toward performance of employees of PT. Kurnia Purnama Jaya. This research was conducted at PT. Kurnia Purnama Jaya  Banda Aceh. As for the object of this study is the information technology, intellectual capital, communication effectiveness, and employee performance organization. The results showed that information technology, intellectual capital, communication effectiveness, and employee performance are already well underway. Then, the test results also showed that information technology and intellectual capital either simultaneously or partially influence the effectiveness of employee communications, information technology and intellectual capital, both simultaneously and partially on the performance of employees, information technology, intellectual capital indirect effect on employee performance through employee communications effectiveness and the effectiveness of communication affect the performance of employees of PT. Kurnia Purnama Jaya  Banda Aceh Keywords: Mastery of Information, Organizational Learning, Employee                     Commitment, Performance of Employees